Animal Feed Additive and the Effect of the Fusarium Toxin Deoxynivalenol on the Electrophysiological Measurement of Transepithelial Ion Transport of Young Chickens with Ussing Chamber Technique - Awad, W.A.; Ghareeb, K.; Bohm, J. (International Journal of Poultry Science, 2008)
The presence of mycotoxins in poultry feeds is a significant factor for financial losses to animal industries. Ingestion of mycotoxin-contaminated feed by chickens causes injury to the gastrointestinal tract. DON has negative effects on the active transport of some nutrients in the small intestine of chickens. We tested the hypothesis that prefeeding with probiotic (Eubacterium sp.) or inulin, as a prebiotic, would attenuate these effects. Whereas, there is evidence in chicken that dietary supplementation with probiotic and prebiotic affect the intestinal microflora, increased the paracellular permeability and increased the villus length and villus area of the small intestine. The question of whether these changes affect the toxic effects of DON on the electrogenic glucose transport in the chicken intestine or not needs to be clarified. Therefore, an experiment was conducted to study the effects of DON in the presence or absence of dietary (Eubacterium sp.) or inulin on the electrophysiological response of the gut to glucose. The results indicated that in the absence of clinical signs and without impaired performance, DON appeared to alter the gut function of broilers. The addition of Eubacterium sp. may be useful in counteracting the toxic effects of DON on intestinal glucose transport. But, the dietary inulin supplementation of the broilers improved the glucose transport in the presence of DON and kept it at normal levels.